Distinct intracellular signaling mediates C‐MET regulation of dendritic growth and synaptogenesis. Issue 10 (11th February 2016) - Eagleson, Kathie L.; Lane, Christianne J.; McFadyen‐Ketchum, Lisa; Solak, Sara; Wu, Hsiao‐Huei; Levitt, Pat
ABSTRACT: Hepatocyte growth factor (HGF) activation of the MET receptor tyrosine kinase influences multiple neurodevelopmental processes. Evidence from human imaging and mouse models shows that, in the forebrain, disruptions in MET signaling alter circuit formation and function. One likely means of modulation is by controlling neuron maturation. Here, we examined the signaling mechanisms through which MET exerts developmental effects in the neocortex. In situ hybridization revealed that hgf is located near MET‐expressing neurons, including deep neocortical layers and periventricular zones. Western blot analyses of neocortical crude membranes demonstrated that HGF‐induced MET autophosphorylation peaks during synaptogenesis, with a striking reduction in activation between P14 and P17 just before pruning. In vitro analysis of postnatal neocortical neurons assessed the roles of intracellular signaling following MET activation. There is rapid, HGF‐induced phosphorylation of MET, ERK1/2, and Akt that is accompanied by two major morphological changes: increases in total dendritic growth and synapse density. Selective inhibition of each signaling pathway altered only one of the two distinct events. MAPK/ERK pathway inhibition significantly reduced the HGF‐induced increase in dendritic length, but had no effect on synapse density. In contrast, inhibition of the PI3K/Akt pathway reduced HGF‐induced increases in synapse density, with no effect on dendritic length. The data reveal a key role for MET activation during the period of neocortical neuron growth and synaptogenesis, with distinct biological outcomes mediated via discrete MET‐linked intracellular signaling pathways in the same neurons. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1160–1181, 2016